1996
DOI: 10.1046/j.1523-1739.1996.10041133.x
|View full text |Cite
|
Sign up to set email alerts
|

Translocations and the Preservation of Allelic Diversity

Abstract: Translocation is a tool commonly used for the conservation of threatened and endangered fish species. Despite extensive use, the biological implications of translocation remain poorly understood. Of particular interest is the effect of translocation on genetic variability. Maintenance of genetic variability in these “refuge” populations is assumed to be important for both short‐ and long‐term success. We examined allozyme variability at 16 loci for western mosquitofish (Gambusia affinis) populations with known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 44 publications
3
85
0
3
Order By: Relevance
“…Indeed, outcrossing may be detrimental for naturally inbred populations (e.g. outcrossed inbred males produce malformed tadpoles in Rana temporaria; Sagvik et al, 2004), particularly when they are outcrossed with captive populations, as demonstrated by the loss, rather than gain of genetic diversity in the Western mosquito fish, Gambusia affinis following the release of fish from captive stocks (Stockwell et al, 1996). There is also evidence from captive studies that establishing populations from multiple stocks can lead to outbreeding depression in the related G. holbrooki (Leberg, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, outcrossing may be detrimental for naturally inbred populations (e.g. outcrossed inbred males produce malformed tadpoles in Rana temporaria; Sagvik et al, 2004), particularly when they are outcrossed with captive populations, as demonstrated by the loss, rather than gain of genetic diversity in the Western mosquito fish, Gambusia affinis following the release of fish from captive stocks (Stockwell et al, 1996). There is also evidence from captive studies that establishing populations from multiple stocks can lead to outbreeding depression in the related G. holbrooki (Leberg, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Pople et al (2001) considered the translocation of animals to Idalia to be a success because the population there was estimated to have increased from 133 founders to in excess of 400 individuals. However, all captive breeding programs are expensive requiring challenging and intensive management to maintain genetic diversity (Stockwell et al 1996) and to ensure that the translocated populations are not overly compromised. Sigg (2006) has subsequently reported progressive genetic loss within the translocated population in Idalia relative to the source population at Taunton National Park.…”
Section: Mono-centric Conservation Of the Bridled Nailtail Wallabymentioning
confidence: 99%
“…Although translocations are a classic solution given the urgency of action required when an organism is declining in number (Griffith et al 1989), there may be detrimental effects of inducing contemporary bottlenecks in already vulnerable species. It is commonly reported that translocation events contribute to the degradation of remaining genetic diversity in historically bottlenecked populations (Stockwell et al 1996;Miller & Lambert 2004;Lambert et al 2005;Olson et al 2013), although this depends on the extent to which genetic diversity has already been depleted (Taylor & Jamieson 2008) (i.e. the variation at some genetic markers may be sufficiently depleted that there is none left to lose).…”
Section: Introductionmentioning
confidence: 99%